2021
DOI: 10.3390/ijerph18116006
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Climate as Social Norm: Impact on Judgements and Behavioral Intentions in the Workplace

Abstract: We present a study that looks at the relationship between the ethical climate, considered as a set of social norms, and judgments and behaviors in the workplace. In this case we think that an ethical rule reflecting the climate is only actualized in conduct and/or decisions if the rule is applicable, is shared, and is the subject of social expectations. A total of 277 professionals responded to a questionnaire measuring the normativity of three ethical rules, socio-moral judgment, trust in supervisors, turnove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…The results of the analysis clearly show that both rule-based and behavior-based ethical climates are significantly associated with job satisfaction, positively influencing job satisfaction levels. This finding aligns with similar studies [55][56][57][58][59][60]66,78,79], which emphasize the importance of the ethical climate as a resource in enhancing nurses' job satisfaction and the effective functioning of healthcare institutions. The indirect effects in the research model were examined, and it was found that the organizational ethical climate and its subdimensions, the ethical climate for rules and the ethical climate for behavior, had a significant effect on job satisfaction in the same direction.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the analysis clearly show that both rule-based and behavior-based ethical climates are significantly associated with job satisfaction, positively influencing job satisfaction levels. This finding aligns with similar studies [55][56][57][58][59][60]66,78,79], which emphasize the importance of the ethical climate as a resource in enhancing nurses' job satisfaction and the effective functioning of healthcare institutions. The indirect effects in the research model were examined, and it was found that the organizational ethical climate and its subdimensions, the ethical climate for rules and the ethical climate for behavior, had a significant effect on job satisfaction in the same direction.…”
Section: Discussionsupporting
confidence: 91%
“…In the same line, Panicker et al [ 17 ] found inclusive practices, inclusive climate, and inclusive leadership to be positively related to organizational citizenship behavior among academicians of a higher education institution in India. Closely related, a recent study by Auzoult and Mazilescu [ 31 ] found ethical climate as a social norm (i.e., as a set of rules perceived as applicable and expected by others) to be positively associated with the intention to rest, trust in a leader, and sociomoral judgment, and negatively to the propensity to discriminate.…”
Section: Introductionmentioning
confidence: 88%
“…They explored the organisational work climate of 117 departments across 103 organisations including for-profit and non-profit companies, public and private organisations, and product-and service-oriented companies. Auzoult and Mazilescu (2021) investigated the similar context of an ethical work climate and surveyed 277 professionals in the transportation, civil services, industry, trade, social, and health sectors. They define ethical climate as a set of behaviours, judgments, and social norms.…”
Section: Introductionmentioning
confidence: 99%